The chemical constituents from twigs of Hamamelis japonica and their antiviral activities. Issue 6 (19th March 2023) - Park, SeonJu; Nhiem, Nguyen Xuan; Song, Jae-Hyoung; Oh, Mira; Kim, Kil-Nam; Ko, Hyun-Jeong; Kim, Seung Hyun
Abstract: Three new monoterpenoid glycosides (1 –3 ) and one new flavanol (4 ) along with 15 known compounds were isolated from the twig of Hamamelis japonica Sieb. et Zucc. The chemical constituent study of the twig of H. japonica has performed for the first time in the present investigation. Their structures were determined based on extensive spectroscopic methods including 1 D and 2 D NMR and CD spectra data. All isolated compounds were tested for their antiviral activities against HRV1B-, EV71-, PR8- and CVB3-infected Vero cells. Among the tested compounds, (–)-epigallocatechin 3- O -gallate exhibited the most consistent and effective antiviral activities against EV71 and PR8 infections. Graphical Abstract: UF0001